Effect of matravasti (medicated oil retention enema) as rasayana (rejuvenative therapy) in jarajanya vikar (problems of aging) - A clinical study - Sathya N Dornala; Om Prakash Sharma (Wolters Kluwer Medknow Publications, 2021)
Introduction: By 2025, there will be 1.2 billion older people in the world, close to three-quarters of them in developing countries, and the WHO estimates that India will have 11% of the total population of senior citizens. The chief aim of geriatrics is to "add life to years" rather than "years to life." If Ayurvedic Rasayana therapy is applied in the true spirit, it is possible to achieve the desired goal. The tremendous potential of Ayurveda may be tapped for the benefits of day-to-day problems of geriatric patients, thereby offering greater and more viable scope for geriatrics in Ayurveda in the future. This study is an attempt in this direction. The objective of the study was to evaluate whether Matravasti shows multiple effects on different bodily systems (Rasayana) for the mitigation of aging-associated problems (Jarajanya vikara). Materials and Methods: Eighty-two patients (56 males + 26 females) suffering from common problems of old age were registered for the study during December 2009 to December 2011 after having informed consent from them, out of which 16 patients (6 males + 10 females) were dropped out. The remaining 66 subjects were studied in detail. Matravasti was administered 21 times with Balashwagandhadi tailam (medicated oil) on alternate days with a dosage of 50-80 ml accordingly (approximately at 1 ml per kg body weight). After the completion of 21 sittings of Matravasti, posttest was done. All the patients were again reviewed after 6 months just to confirm the sustainability of the Matravasti effects. Fourteen clinical parameters involving different systems were considered for pretest and posttest assessment based on the available standard scales and self-rated scores to see the effect of Matravasti. Results and Discussion: Among all clinical parameters considered for the study, maximum improvement was found in sleep disturbances (67.5%) followed by gait balance deficit (56.25%), emotional status (55.1%), urinary incontinence (55%), mobility (53.96%), instrumental activities of daily living (IADL) (51.3%), ADL (50.8%), constipation (49.5%), cognitive status (48.78%), pain (48.14%), dyspnea (47.25%), hearing impairment (42.5%), visual impairment (41.8%), dermatological manifestations (41.17%), and involuntary movements (22.2%). Patients also found a positive effect on their associated complaints such as hypertension, gastric troubles, loss of appetite, dementia, and parkinsonism. Conclusion: The overall effect observed after this trial was Fair (25%-50% of improvement) in 38 cases, Good response (51-75% response) in 26 cases, and the Best response (>75%) in 2 cases. Moreover, the maximum benefit observed among all the cases was 81.8% and the least effect was 25%. After the study, it is evident that Matravasti, particularly with Balashwagandhadi tailam, shown multifaceted action (due to Rasayana property) and is a highly appreciated therapeutic measure in geriatric conditions.